2019
DOI: 10.3389/fimmu.2019.00423
|View full text |Cite
|
Sign up to set email alerts
|

Caught in a Trap? Proteomic Analysis of Neutrophil Extracellular Traps in Rheumatoid Arthritis and Systemic Lupus Erythematosus

Abstract: Neutrophil Extracellular Traps (NETs) are implicated in the development of auto-immunity in diseases such as rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) through the externalization of intracellular neoepitopes e.g., dsDNA and nuclear proteins in SLE and citrullinated peptides in RA. The aim of this work was to use quantitative proteomics to identify and measure NET proteins produced by neutrophils from healthy controls, and from patients with RA and SLE to determine if NETs can be differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
147
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(171 citation statements)
references
References 141 publications
(192 reference statements)
14
147
0
1
Order By: Relevance
“…In addition, subclinical kidney injury may readily be missed until consecutive exposures to UV light compound the effects. While we found that neutrophil-mediated kidney inflammation in response to UV light does not cause clinical disease in healthy mice, such a mechanism may contribute to LN flares in photosensitive lupus patients in multiple ways: Fc receptor engagement by immune complexes could enhance neutrophil recruitment resulting in ROS and protease release 105,106 ; the heightened capacity of lupus neutrophils and LDGs to produce NETs, which in SLE patients are not cleared efficiently 107,108 , could lead to release of tissue-damaging proteases 109,110 , propagation of the IFN-I response 85,86 , or direct damage to the kidney endothelium by creating vascular damage and leakage 14,111 . Moreover, the underlying differences in lupus skin, such as enhanced IFN-I signaling 7,112,113 and defects in protective Langerhans cell population 114 could inform the extent and nature of neutrophil-mediated systemic responses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, subclinical kidney injury may readily be missed until consecutive exposures to UV light compound the effects. While we found that neutrophil-mediated kidney inflammation in response to UV light does not cause clinical disease in healthy mice, such a mechanism may contribute to LN flares in photosensitive lupus patients in multiple ways: Fc receptor engagement by immune complexes could enhance neutrophil recruitment resulting in ROS and protease release 105,106 ; the heightened capacity of lupus neutrophils and LDGs to produce NETs, which in SLE patients are not cleared efficiently 107,108 , could lead to release of tissue-damaging proteases 109,110 , propagation of the IFN-I response 85,86 , or direct damage to the kidney endothelium by creating vascular damage and leakage 14,111 . Moreover, the underlying differences in lupus skin, such as enhanced IFN-I signaling 7,112,113 and defects in protective Langerhans cell population 114 could inform the extent and nature of neutrophil-mediated systemic responses.…”
Section: Discussionmentioning
confidence: 99%
“…The property of neutrophils to release extracellular traps was not conducive to the clinical development of RA [19]. It is well-known that a large number of neutrophils accumulate in the synovial tissue of RA, which spontaneously released neutrophil extracellular traps (NETs) [20]. NETs, a network structure consisted of DNA and granulose, could indirectly impair the endothelial function,promote blood vessel and glomerular damage, thus it would induce renal failure and even death [21].…”
Section: Discussionmentioning
confidence: 99%
“…The protein cargo of NETs induced by different stimuli is heterogenous, making comparing research and drawing conclusions challenging. Due to this, there is an ongoing discussion about the precise mechanisms involved in NET formation, their composition and, thereby, their functional profile specifically their inflammatory/antimicrobial properties [6,9,10]. Recently, there have been new insights about how molecular mechanisms of NET formation may differ in a species specific manner [11,12] but, also based on the location of neutrophils in the blood stream or tissue, as well as local environmental alkaline or oxygen conditions [13].…”
Section: Composition Of Neutrophil Extracellular Traps (Nets)mentioning
confidence: 99%